Upholding the Rights of Persons with Disabilities Through the Difference Principle - Miftakhul Shodikin; Syofyan Hadi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The right to work is a right for every citizen to earn a decent living for humanity. However, injustice is still often felt by people with disabilities who often face challenges in accessing this right. The difference principle asserts that inequality is only acceptable if it provides the greatest benefit to the most disadvantaged. This principle is an appropriate analytical tool to evaluate how employment policies in Indonesia have succeeded in minimizing the inequalities faced by persons with disabilities. Therefore, this research aims to explain the difference principle prioritizes the well-being of those who are most disadvantaged or marginalized. This study aims to analyze the legal issues through a normative legal lens, incorporating both statutory and conceptual analysis. Through normative analysis and deductive reasoning, the result of this research is that the regulation of the right to work for persons with disabilities is not yet optimal in accordance with the difference principle. Such as special quota policies that are not accompanied by strict sanctions, training, and job fairs that are still general and have yet to fully meet the unique requirements of individuals with disabilities. The inclusive recruitment process, which should be a must, is a phrase in the article that regulates the possibility (optional) instead of an obligation (mandatory). Meanwhile, the limited authority of the Disability Service Unit (ULD) in the employment sector and the weak institutional structure of the National Commission on Disability (KND), which is far from independent, include the barriers that individuals with disabilities encounter in accessing their right to employment.